Inducible gene expression in GFAP+ progenitor cells of the SGZ and the dorsal wall of the SVZ: a novel tool to manipulate and trace adult neurogenesis - Weber, Tillmann; Baier, Vera; Pauly, Rahel; Sahay, Amar; Baur, Max; Herrmann, Elke; Ciccolini, Francesca; Hen, René; Kronenberg, Golo; Bartsch, Dusan (Glia, 2011)
In the adult mammalian brain, neurogenesis originates from astrocyte-like stem cells. We generated a transgenic mouse line in which the tetracycline dependent transactivator (tTA) is expressed under the control of the murine GFAP promoter. In this mouse line, inducible gene expression targets virtually all GFAP-expressing stem-like cells in the dentate gyrus and a subset of GFAP-expressing progenitors located primarily in the dorsal wall/dorsolateral corner of the subventricular zone. Outside the neurogenic zones, astrocytes are infrequently targeted. We introduce a panel of transgenic mice which allow both inducible expression of candidate genes under control of the murine GFAP promoter and, at the same time, lineage tracing of all cells descendant from the original GFAP-positive cell. This new mouse line represents a versatile tool for functional analysis of neurogenesis and lineage tracing. © 2011 Wiley-Liss, Inc.